The Malaysian employees provident fund’s members’ investment scheme: survey of fund selection, performance and perceptions / Agnes Paulus Jidwin, Jasman Tuyon and Rosalan Ali - Jidwin, Agnes Paulus; Tuyon, Jasman; Ali, Rosalan (Universiti Teknologi MARA Cawangan Selangor, 2011)
This study examines whether the Employee Provident Fund members investment scheme (EPF-MIS) introduced by EPF could provide better performance than the EPF retirement plan itself. Statistics have revealed that the average retirement savings of EPF members currently are inadequate and many members may find themselves with insufficient funds if the issue of adequacy of savings is not addressed. To partly address the above-mentioned issues, EPF introduced the investment withdrawal scheme in 1996 to enhance retirement savings. However, participating members were concerned when it was reported that members had suffered losses of about RM600 million in unit trust investments, contradicting the good performance of the unit trust funds industry. Thus, this paper attempts to revisit these issues by conducting a structural survey analysis on EPF members’ investment in unit trusts, based on strategies, unit trust performance and members’ perceptions. This study involved 310 respondents, covering all states in Malaysia. Collectively, findings revealed that members’ experiences of investment performances in unit trusts were mixed. The highest return on members’ investment was 10% and lowest return was negative 5%. This provides evidence to show that there are possibilities of the participating members’ earnings falling below the 2.5% guaranteed minimum return for EPF. From the opportunistic point of view, there are also possibilities for members to generate higher returns than the average performance of EPF investment of 5% with appropriate fund selection strategies as discussed in this paper. It is concluded that members’ investment performance is influenced by their level of knowledge of unit trust investment, information source as well as fund selection criteria. Additionally, financial consultants play a critical role in assisting EPF members with their investment decision making, since the majority of them are relying on services and advice rendered by financial consultants. Recommendations are drawn on EPF members’ perceptions and industry best practices, and given for future research.